Dimensionen narrativer Sinnstiftung im frühneuhochdeutschen Prosaroman : Textgeschichtliche Interpretation von 'Fortunatus' und 'Herzog Ernst'. - Speth, Sebastian (Frühe Neuzeit., 2017)
In historical and cultural studies, the Early Modern Age has developed a profile of its own. The book series Frühe Neuzeit (Early Modern Age) publishes editions, monographs and collected volumes advancing fundamental research in the field. It does not seek to produce wide-ranging overviews, premature syntheses or pretentious constructions but takes the long route of detailed work and the exploration of submerged traditional linkages. Particular emphasis is placed on studies which transcend the boundaries of individual disciplines.